Accurate finite element modelling of knots and related fibre deviations in structural timber - Khaled Saad; András Lengyel (Journal of King Saud University. Engineering sciences, 2024)
The primary purpose of the pursued research presented in this article was to propose a new technique to create the actual three-dimensional geometry of knots and related fibre deviations and eliminate the inconsistency between modelling the knots as openings or solids. The geometrical and mechanical characteristics of knots and related local disturbed fibre patterns were numerically modelled. The numerical models were experimentally validated by four-point bending tests performed on six timber beams made of Nordic spruce (Picea abies). Tested specimens were sliced up into several strips parallel to the grains in the vicinity of the knot to numerically generate the actual geometrical model of the knots and related fibre deviations for creating the three-dimensional fibre paradigm. The validated numerical models can also be used based on visual inspections. The user needs only to define the position and size of the knot within the timber element required for the 3D finite element model. Moreover, the model allows defining different fibre patterns in the knot vicinity. Results proved that openings can represent knots when found in the tension zone with careful adjustment of the related three-dimensional fibre deviations. Moreover, the results emphasize the need for accurate modelling for the fibre deviations rather than the knot itself.